Composition, Physicochemical Properties, and Uses of Acorn Starch - Mehdi Taib; Lahboub Bouyazza (Journal of Chemistry)
The major component of acorn is starch, which may amount up to 55% of the dry weight. Lack of systematic knowledge on acorn starch greatly hinders the further development of acorns as sustainable crops. This review aims to summarize the current knowledge of the isolation, chemical composition, physicochemical properties, and uses of acorn starches and to provide future research directions. The amylose content of the acorn starches is reported to vary in the range of 20–39%. Moisture content, lipid, ash, and protein contents of the acorn starches have been reported varying from 2.20 to 15.50%, 0.23 to 2.64%, 0.01 to 1.41%, and 0.01 to 6.7%, respectively. Thermal and pasting properties that have usually been determined using differential scanning calorimeter (DSC) and rapid viscoanalyzer (RVA) are also discussed in this article. Acorn starch has great potential for various food and nonfood applications due to the unique structural and functional features.